Hypertriglyceridemia Induced Acute Pancreatitis: A Learn from New Cases (Sciences of Pharmacy, 2023)
An increased risk of morbidity and mortality is associated with acute pancreatitis (AP) brought on by hypertriglyceridemia (HTG). It is essential to locate the root cause as soon as possible and give those affected the attention they need. The treatment plan includes efforts to lower blood triglyceride levels and supportive care. HTG-induced AP has a similar clinical course to people with other types of acute pancreatitis. However, HTG-induced AP patients have significantly higher clinical severity and associated consequences. As a result, therapy and preventing sickness recurrence depend on a correct diagnosis. At the moment, there are no acknowledged standards for the treatment of HTG-induced AP. Some therapy approaches that effectively decrease serum triglycerides include fibric acids, apheresis/plasmapheresis, insulin, heparin, and omega-3 fatty acids. Following acute phase care, lifestyle modifications, including dietary and drug therapy, are essential for long-term HTG-induced AP control and relapse prevention. To create complete and efficient HTG-induced AP treatment guidelines, more study is required.